Perancangan Brand Identity Home Spa Laksmi Sebagai Upaya Meningkatkan Brand Awareness - Bara, Anggelina Paskalia; Budiardjo, Hardman; Yuan, Dhika (Jurnal Art Nouveau, 2017)
Home Spa Laksmi is one of the platform of “Laksmi Kebaya Muslimah & Islamic Wedding Service” a service is still much that needs to explore and developed. This study aims to build brand identity Home Spa Laksmi that the public especially people in Surabaya is known to the services of Laksmi, especially the Home Spa Laksmi. In the design process she needs to find an identity company. What are the company will have a relationship with the company's image, so that the identity of the company is important to note from the beginning. In addition, Home Spa Laksmi has value and make a difference in all the elements, so it's a thing called the process of branding or design brand identity.Some of the methodology of research that the methodology of a qualitative among others including observation, interviews, the competitors, techniques to analyze data, the reduction of data, the withdrawal of the conclusion. To support the process of design, brand identity Home Spa Laksmi. From the results of the data then the concept of the obtained is a Lifestyle, which is in accordance with the values of Islamic. So, brand identity Home Spa Lakshmi that was designed by researchers were able to be one of the evidence his appreciation to the values of Islamic Keywords: Brand Identity, Home Spa Laksmi, Brand Awareness, Surabaya